2016
DOI: 10.1289/ehp.1510090
|View full text |Cite
|
Sign up to set email alerts
|

Inorganic Arsenic–Related Changes in the Stromal Tumor Microenvironment in a Prostate Cancer Cell–Conditioned Media Model

Abstract: Background:The tumor microenvironment plays an important role in the progression of cancer by mediating stromal–epithelial paracrine signaling, which can aberrantly modulate cellular proliferation and tumorigenesis. Exposure to environmental toxicants, such as inorganic arsenic (iAs), has also been implicated in the progression of prostate cancer.Objective:The role of iAs exposure in stromal signaling in the tumor microenvironment has been largely unexplored. Our objective was to elucidate molecular mechanisms… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 59 publications
1
15
0
1
Order By: Relevance
“…Interestingly, the changes we identified in our differentiationspecific gene panels mirrored the changes detected in TGFb expression as assessed by RT-qPCR. We have shown in previous studies that iAs is able to alter TGFb signaling in human ASCs in vitro (Shearer et al, 2016), which might explain the concentration-dependent decrease in osteogenic/chondrogenicrelated genes seen in the present study.…”
Section: Discussionsupporting
confidence: 73%
See 3 more Smart Citations
“…Interestingly, the changes we identified in our differentiationspecific gene panels mirrored the changes detected in TGFb expression as assessed by RT-qPCR. We have shown in previous studies that iAs is able to alter TGFb signaling in human ASCs in vitro (Shearer et al, 2016), which might explain the concentration-dependent decrease in osteogenic/chondrogenicrelated genes seen in the present study.…”
Section: Discussionsupporting
confidence: 73%
“…The remaining mice (N ¼ 3, per exposure) continuously received iAs H 2 O for 3 more weeks in order to monitor the stability of urinary arsenic levels over time. We chose these concentrations by mimicking the exposure required to induce a similar induction in heme-oxygenase 1 gene expression in mouse ASCs (300 ppb) relative to human ASCs (75 ppb) in vitro (data not shown), which we previously have suggested plays a role in altering ASC signaling (Shearer et al, 2016). Exposure to 75 ppb iAs in humans represents a high level of arsenic that exceeds the safety limit set by the EPA but is not uncommon in certain portions of the world including Bangladesh who are at times exposed to levels of iAs exceeding 300 ppb (Smith et al, 2000).…”
Section: Animals and Arsenic Exposurementioning
confidence: 99%
See 2 more Smart Citations
“…Based on these studies several mechanisms of arsenic-induction of prostate cancer have been proposed including overexpression of matrix metalloproteinase-9, heme oxygenase-1, and ras, the decreased expression of thrombospondin, and the induction of acquired androgen independence (Benbrahim-Tallaa and Waalkes, 2008; Benbrahim-Tallaa et al, 2005; Benbrahim-Tallaa et al, 2007; Witz, 2008). In a recent study, the alteration of stromal TGFβ signaling by arsenic exposure was shown to be related to progression of prostate cancer (Shearer et al, 2016). …”
Section: Discussionmentioning
confidence: 99%